Molecular cloning and expression of a putative crustacean hyperglycemic hormone (CHH) of Litopenaeus vannamei in Pichia pastoris - Sánchez-Castrejon, Edna; Ponce-Rivas, Elizabeth; Aguilar, Manuel B.; Díaz, Fernando (Electronic Journal of Biotechnology, 2008)
Crustacean hyperglycemic hormone (CHH) is the most abundant and best studied member of the CHH/MIH/GIH neuropeptide hormone family. CHH plays a major role in controlling glucose levels in the hemolymph, and it also has significance in regulating molting, reproduction, and osmoregulation. In contrast, molt inhibiting hormone (MIH) is responsible for maintaining animals in an intermolt stage. In this study, Liv-MIH-1 cDNA, which encodes a mature neuropeptide from the eyestalk of white shrimp, Litopenaeus vannamei, was expressed in methylotrophic yeast (Pichia pastoris KM71) under the control of an alcohol oxidase promoter. Recombinant Liv-MIH-1 was secreted into the culture medium using the α-factor prepro-sequence without Glu-Ala repeats. The expected protein, which had an apparent molecular mass of 12.1 kDa, was detected by Tricine-SDS-PAGE analysis and confirmed by Western blot. Pure recombinant Liv-MIH-1 was obtained by affinity chromatography, and N-terminal sequence analysis confirmed expression of the protein. Biological assays for CHH and MIH activity were also performed. Purified recombinant Liv-MIH-1 showed the ability to elevate the glucose level of hemolymph of L. vannamei, but molting was unaffected. These results are in agreement with the high structural and phylogenetic similarity that has been observed between Liv-MIH-1 and other CHH neuropeptides.